Steppenwolf - Hesse, Hermann, 1877-1962 (Penguin Books, 2025)
"Nobel Prize winner Hermann Hesse's iconic countercultural novel about the search for authenticity in an inauthentic world, in a new translation A Penguin Classic At first glance, Harry Haller seems like a respectable, educated man. In reality, he is the Steppenwolf: wild, strange, alienated from society, and repulsed by the modern age. But as he is drawn into a series of dreamlike and sometimes savage encounters-accompanied by, among others, Mozart, Goethe, and the bewitching Hermione-the misanthropic Haller undergoes a spiritual, even psychedelic, journey, and ultimately discovers a higher truth and the possibility of happiness. This blistering portrait of a man who feels himself to be half human and half wolf was the bible of the 1960s counterculture, capturing the mood of a disaffected generation. It continues to resonate as a haunting story of estrangement, redemption, and the search for one's place in the world"--